Implementasi Kebijakan Retribusi Parkir Berdasarkan Peraturan Daerah Nomor 1 Tahun 2024 Tentang Pajak Daerah Dan Retribusi Daerah Kabupaten Sekadau - Hermansyah M; Zulkarnaen Zulkarnaen; Ahmad Tohardi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The problems in this research stem from the weak and indecisive enforcement by parking attendants in collecting public roadside parking fees from vehicle owners when performing their duties, the delay in depositing funds from parking attendants to the Regional Cash Revenue Treasurer, the fact that many people are reluctant to pay parking fees, the population density levels not increasing significantly, the maximum non-implementation of the SOP for public roadside parking fees, and the fact that many people are unaware of the parking tariff increase in accordance with Regional Regulation Number 1 of 2024 concerning Regional Taxes and Regional Levies of Sekadau Regency. The objective of this research is to describe and analyze the implementation process of parking fees based on Regional Regulation Number 1 of 2024 concerning Regional Taxes and Regional Levies of Sekadau Regency at the Sekadau Regency Transportation Agency. This research uses a descriptive research method with a qualitative approach. The results of this study show that the implementation of public roadside parking fee collection still faces various obstacles in the field, such as lack of socialization to the public about the applicable tariffs, the manual collection system, the lack of public awareness to pay fees, the limited human resources for supervision, the persistence of illegal parking, and the lack of adequate parking facilities.